Obadiah - Becking, Bob (Oxford University Press, 2021)
This essay touches on three topics: (1) the relation between Obadiah and Jeremiah not as an instance of one prophet quoting the other but as an example of both prophets quoting a traditional anthem; (2) the animosity between Edom and Judah in the book of Obadiah as not referring to Edom’s role during the Babylonian conquest of Jerusalem but reflecting postexilic struggles after the Edomite occupation of Southern Judah; and (3) Obadiah’s conceptual coherence as a separate book. The contribution ends with a few hermeneutical remarks on the violent character of vengeance.
Keywords: Conquest of jerusalem; Edom; Intertextuality; Jeremiah; Obadiah; Vengeance; Violence; Taverne; General Arts and Humanities; SDG 16 - Peace, Justice and Strong Institutions